2007
DOI: 10.1007/s11094-007-0096-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of analytical methods for hydrochloride salts of cardiocyclide, a new Russian class III antiarrhythmic

Abstract: Cardiocyclide, a new Russian class III antiarrhythmic agent, was developed at the State V. V. Zakusov Science Research Institute Pharmacology, Russian Academy of Medical Sciences. The aims of the present work were to study the physicochemical properties of the hydrochloride salt of this agent (N 1 -(3-diethylaminopropyl)-N 1 -(p-nitrobenzoyl)aminoacetic acid N,N-dicyclohexylamide HCl) and to develop an analytical method for this compound. IR, 1 H NMR, and UV spectra were obtained for cardiocyclide; its solubil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…However, the previous results indicated that processing impurities of the two last synthetic steps (II and III) in addition to unidentified impurities could not be completely separated using TLC [2]. Therefore, a decision was made to use HPLC, which is more sensitive and selective, to analyze the purity of both the drug substance and the medicinal form of I.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the previous results indicated that processing impurities of the two last synthetic steps (II and III) in addition to unidentified impurities could not be completely separated using TLC [2]. Therefore, a decision was made to use HPLC, which is more sensitive and selective, to analyze the purity of both the drug substance and the medicinal form of I.…”
Section: Resultsmentioning
confidence: 99%
“…(100:50:3) and the method developed earlier for the drug substance of I [2]. Adsorption bands were detected using UV light at wavelength 254 nm and iodine vapor.…”
Section: Experimental Partmentioning
confidence: 99%
See 1 more Smart Citation